Evaluation of a Climate change-Adaptive, Eco-Friendly Agronomic Package for Potato (Solanum tuberosum L.) Cultivation in the Farmer Fields of the Jaffna District of Sri Lanka . - Eeswaran, R.; De Costa, W.A.J.M.; De Costa, D.M.; Dandeniya, W.S.; Sivakumar, S.; Suriyagoda, L.D.B. (Tropical Agricultural Research, 2016)
Potato is one of the key annual upland cash crops cultivated in the Jaffna District of Sri Lanka. However, potato farmers are challenged by climate extremes, increasing pest/disease loads and excessive use of agro-chemicals all of which are expected to increase in the future. To address these critical issues, a package of climate change adaptive and eco-friendly agronomic practices that included mulching to conserve soil moisture, integrated pest management for crop protection and site-specific fertilizer management for efficient crop-soil nutrient management (adaptation package) was formulated and tested on potato (Solanum tuberosum L.) crops in seven farmer fields in Jaffna. The experiment was conducted in the major rainy season (Maha) of 2013/2014 and 2014/2015 and consisted of two treatments as Adaptation package (T1) and Existing practice (T2), which is the current farmers’ practices characterized with heavy reliance on chemical control of pests and diseases and application of inorganic fertilizers subsequent to decisions of farmer. The results revealed significant (p<0.05) benefits of the above climate change adaptive, eco-friendly agronomic package in terms of growth, yield, economic profit and environmental health of potato cultivation. Benefits of the adaptation package were greater in the drier and warmer 2014/15 Maha season, thus demonstrating its climate resilience. Therefore, the tested adaptation package can be recommended for adoption by the farmers to improve the yield of potato while promoting lower water and agro-chemical use thereby having increased resilience to climate change and improved environmental sustainability especially in the dry regions where potato is cultivated.
Keywords: Adaptation package; Integrated pest management; Mulching; Potato; Site-specific fertilizer management